Soil depth and soil production. Issue 6 (11th March 2015) - Hunt, Allen G.
Abstract : Soil column depth is predicted over time scales up to a million years based on dynamics at the pore scale. The power law result integrates result for solute transport from percolation theory with typical flow velocities. Verification was based on studied soils from 14 regions worldwide over time scales from decades to a million years. The time derivative of the soil depth generates the soil production function as a function of depth. Comparison with soil production data from five locations, over similar time scales, verifies the accuracy of the predicted power to within 2%. The prediction thus unites within one framework time scales of seconds with a million years. The results allow calculation of the effects of physical soil removal on the rates of silicate weathering at the base of the column, important inputs to the global carbon cycle, neotectonics, and drainage basin evolution. © 2015 Wiley Periodicals, Inc. Complexity 21: 42–49, 2016